Unveiling India's Defense Modernization Under Modi Administration: Navigating Regional Geopolitical Challenge - Rivai, Aspin Nur Arifin (Jurnal Studi Diplomasi dan Keamanan, 2025)
This study explores India’s defense modernization and strategic recalibration in response to China's growing geopolitical influence, particularly since 2014. The main goal is to analyze India’s evolving military doctrine, defense modernization efforts, and the integration of technological advancements to counter regional threats and strengthen its strategic position. A qualitative research design is employed using a case study approach. Secondary data from government reports, defense policy documents, and scholarly articles are analyzed through thematic and content analysis methods, enabling a comprehensive understanding of India’s defense strategies. India’s military doctrine has shifted from a South Asia-centric approach to embracing a broader Indo-Pacific framework. The "Make in India" and "Atmanirbhar Bharat" initiatives emphasize self-reliance, reducing dependency on foreign arms. Technological advancements in artificial intelligence, autonomous systems, and cybersecurity are central to India’s defense modernization. Strategic partnerships with countries like the United States and Israel have strengthened India’s military capabilities. However, challenges remain in bureaucratic inefficiencies, technological integration, and domestic defense industry development. India’s defense modernization is part of a proactive strategy aimed at long-term strategic autonomy and regional influence. This study contributes to a deeper understanding of India’s evolving defense strategy, blending technological innovation with geopolitical dynamics.